Effectiveness of musical activities on the executive functions of students with Educable Intellectual Disability - Majid Ebrahimpour; Zahra Izadi (Ravānshināsī-i Afrād-i Istis̠nāyī, 2019)
Present study aimed to determine efficacy of musical activities on executive functions students with educable intellectual disability. This study was a quasi-experimental method with pretest-posttest and a control group design. Statistical population included all students with educable intellectual disability 11-14 years of old from two exceptional schools in Karaj sity in the academic year 1395-96. 30 students were selected from the population through available sampling method and randomly allocated to either a control or experimental group (n=11). meantime the study, 4 students from experimental group and 4 from control group left the intervention(n=11). The experimental group participated at 24 group sessions of one hour musical activities 3-time per week for 8 weeks. The control group did not receive any intervention along with this period. All participants administered computerized Wisconcin Card Sorting Test (WCST), to assessing cognitive flexibility; Go/no Go Test, to assessing inhibitory control; and Digit Span Subtest of WISC-IV, to assessing working memory, befor and after the intervention. Results of data analyzing through Covariance analysis indicated that, there was no differences between post-test scores at the level of ?=0/05. This means that these musical activities program has had not a significant effect on improvement of experimental group functioning on administered executive functions tests.